2010
DOI: 10.1097/hp.0b013e3181e28cdb
|View full text |Cite
|
Sign up to set email alerts
|

Image Quantification for Radiation Dose Calculations—limitations and Uncertainties

Abstract: Purpose-Radiation dose calculations in nuclear medicine depend on quantification of activity via planar and/or tomographic imaging methods. However, both methods have inherent limitations, and the accuracy of activity estimates varies with object size, background levels, and other variables. The goal of this study was to evaluate the limitations of quantitative imaging with planar and SPECT approaches, with a focus on activity quantification for use in calculating absorbed dose estimates for normal organs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…These include 111 In-labeled antibodies and tumor-seeking radiopharmaceuticals (37)(38)(39), 131 I uptake in tumors (40,41), 177 Lu for dosimetry calculations in therapeutic applications (42,43), 186 Re in palliative bone cancer therapy (44), and even quantitative bremsstrahlung imaging of 90 Y (45).…”
Section: Results Demonstrating Quantitative Accuracy In Spectmentioning
confidence: 99%
“…These include 111 In-labeled antibodies and tumor-seeking radiopharmaceuticals (37)(38)(39), 131 I uptake in tumors (40,41), 177 Lu for dosimetry calculations in therapeutic applications (42,43), 186 Re in palliative bone cancer therapy (44), and even quantitative bremsstrahlung imaging of 90 Y (45).…”
Section: Results Demonstrating Quantitative Accuracy In Spectmentioning
confidence: 99%
“…Planar imaging method has the limitation that it represents a 3D distribution of radioactivity in a 2D display, causing difficulty in accurate localization and errors in radiotracer quantification. 68,69 The high radiation absorbed dose calculated for the different organs in the present study could be due to the low resolution of the planar images leading to overestimation of the radiotracer activity in the target organ. Also, the high radiation absorbed dose calculated in heart and lungs may be due to the blood pool in these organs for which no correction was applied during image quantification.…”
mentioning
confidence: 89%
“…Hepatic intraarterial 99m Tc-MAA scintigraphy is a validated means of simulating the 90 Y radioembolization therapy field (13,14). SPECT/CT-based dosimetry is superior to planar scintigraphy by tomographically resolving overlapping radiotracer activity, evaluating heterogeneous radiotracer uptake, and detecting activity in small lesions (12,14,17). Phantom studies have shown that 99m Tc-MAA SPECT/CT volume measurements are accurate and reproducible (13).…”
mentioning
confidence: 99%
“…SPECT/CT is superior to both planar scintigraphy and SPECT for assessing intrahepatic biodistribution of 99m Tc-macroaggregated albumin ( 99m Tc-MAA), and for estimating the tumor-to-normal liver (T/ N) ratio (12)(13)(14). The partition model is a validated dosimetric method for 90 Y resin microspheres, scientifically superior to the body surface area (BSA) method (5,10).…”
mentioning
confidence: 99%